2005
DOI: 10.4161/cc.4.10.2061
|View full text |Cite
|
Sign up to set email alerts
|

Low Concentrations of Taxol Cause Mitotic Delay Followed by Premature Dissociation of p55CDC from Mad2 and BubR1 and Abrogation of the Spindle checkpoint, Leading to Aneuploidy

Abstract: Taxol is widely used for the treatment of human cancer. Its mechanism of action in cells is dependent on drug concentration. At low concentrations of Taxol (5-10 nM), cells exhibit aberrant mitosis, including aneuploidy, in the absence of mitotic arrest. At higher concentrations of Taxol (>20 nM), the cell cycle is blocked at metaphase by spindle checkpoint activation. Here we demonstrate that low concentrations of Taxol cause mitotic delay, and result in an aneuploid population of cells after exit from mitosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 14 publications
5
68
1
1
Order By: Relevance
“…To determine if the lack of mitotic arrest in arsenite-resistant cell lines was due to decreased spindle checkpoint function, all four melanoma cell lines were treated with the spindle checkpoint-activating agent paclitaxel (Ikui et al, 2005) ranging from 0 to 300 nM and mitotic indices were determined after 24 h of treatment. Paclitaxel caused a robust increase in the mitotic index of arsenite-sensitive A375 and SK-Mel-2 cells with a concentration of 100 nM paclitaxel increasing the mitotic index to 61 and 40%, respectively ( Figure 7A).…”
Section: Resultsmentioning
confidence: 99%
“…To determine if the lack of mitotic arrest in arsenite-resistant cell lines was due to decreased spindle checkpoint function, all four melanoma cell lines were treated with the spindle checkpoint-activating agent paclitaxel (Ikui et al, 2005) ranging from 0 to 300 nM and mitotic indices were determined after 24 h of treatment. Paclitaxel caused a robust increase in the mitotic index of arsenite-sensitive A375 and SK-Mel-2 cells with a concentration of 100 nM paclitaxel increasing the mitotic index to 61 and 40%, respectively ( Figure 7A).…”
Section: Resultsmentioning
confidence: 99%
“…The chemotherapeutic drug Taxol triggers cell death by inactivating the spindle checkpoint, thus inducing aneuploidy and aberrant mitosis (39). Kinase inhibitors that have the same effects on tumor cells might therefore be helpful adjuncts when used in combination with chemotherapeutic drugs based on other strategies.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that paclitaxel's induction of apoptosis can occur due to aberrant mitosis or to entering a multinucleated G1-like state subsequent to mitotic slippage, depending on cell type and drug schedule (Abal et al, 2003). A recent study reported that high paclitaxel treatment causes well sustained spindle checkpoint activation leading to mitotic block, while low concentrations below 10 nM cause mitotic delay but premature abrogation of the spindle checkpoint leading to aneuploidy (Ikui et al, 2005). We observed a similar phenomenon comparing low and high paclitaxel levels (supplementary data).…”
Section: Discussionmentioning
confidence: 99%